Analisis Kelayakan Investasi Penambahan Alat Berat dengan Pendekatan Aspek Finansial - Salsabilla, Shopia; Marliana, Wahyuningrum (Journal of Business and Economics Research (JBE), 2024)
This research aims to analyze the feasibility of adding one Sunward brand SWE210 type excavator unit at PT Mahakam Jaya Perkasa in Sangasanga, East Kalimantan. This research uses quantitative method with field techniques and literary technique as data collection technique. The sampling uses financial reports, such as balance sheets, profit and loss, and cash flow. The data analysis techniques use are Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Payback Period (PP). The research results use the Net Present Value (NPV) method shows that the total PV Cash Flow is IDR 1.765.401.658. At the same time, the amount of investment proposed by the company is IDR 1.100.000.000 and the resulting Net Present Value is IDR 665.401.658, with Internal Rate of Return (IRR) amounting to 17,853% greater than the Discount Factor value of 17%, the Profitability Index (PI) value is 1,60 which can be said to be greater than 1. The Payback Period (PP) has a result of 7 months with a long economic investment period of 5 years. So, it can be said that the investment is feasible.